Cross River State Grown Andrographis paniculata Ethanol Leaf Extract Attenuates Insulin Resistance and TNF Alpha in Obese Rats - Ati, B. U.; Asuk, A. A.; Dasofunjo, K. (African Journal of Biochemistry and Molecular Biology Research, 2025)
This study investigated the ethanol leaf extract of Andrographis paniculata and its potential role in attenuating insulin resistance and decreasing turmor necrosis factor alpha levels, raised in obese condition. Twenty five (25) rats were grouped into five (5); Group I: served as normal control and received normal saline and normal rats pellet, Group II: served as obesity control and was fed a high-fat diet but not treated, Group III: served as positive control, fed with a high-fat diet and 30 mg/kg body weight Orlistat, Group IV: fed with a high-fat diet and treated with 500 mg/kg body weight A. paniculata, and Group V: fed with a high-fat diet and treated with 1000 mg/kg body weight A. paniculata. The results showed significant (P<0.05) increases in both TNF-α and HOMAR-IR index in obese rats but decreased in obese rats treated with 30 mg/kg bw Orlistat, 500 and 1000 mg/kg bodyweight A. paniculata. It can be concluded, that A. paniculata has properties that could play a role in attenuating insulin resistance and inflammation induced by obesity.